The Relevance of Islamic Values in the Javanese-Sunda Customary Marriage Tradition - Zain, Muhammad Fuad; Gusti, Iman Yanuar Kinasih (International Journal of Social Science and Religion (IJSSR), 2025)
This study aims to analyze the relevance and implementation of Islamic values ​​in Javanese-Sundanese traditional marriage traditions in Brebes, by comparing ideal norms with socio-cultural practices prevailing in the community. In this context, Islamic values ​​serve as normative guidelines that Influence the marriage process, while Javanese-Sundanese customs, as part of local culture, influence various stages of the procession. This study used a qualitative approach with observation and in-depth interviews involving marriage participants, traditional leaders, and religious figures. Data were analyzed using a socio-cultural approach to understand the extent to which Islamic values ​​are applied in marriage traditions and how the community balances religious demands with local wisdom. The results show that although Islamic norms are generally respected, there are several adjustments in Javanese-Sundanese traditional marriage practices. This reflects the community's efforts to maintain its cultural identity while still fulfilling religious demands. These findings emphasize the importance of understanding the relationship between religion and culture in creating social harmony.